Determinants of local government performance: evidence from Indonesia - Salsabila, Sylvia Aida; Rochmatullah, Mahameru Rosy (Institute of Computer Science (IOCS), 2024)
This study explores local government performance from the perspectives of human resources and public welfare, providing evidence from various regions in Indonesia. Performance is the outcome of a lengthy process of activities. This research aims to investigate local government performance, given the ongoing questions about whether governmental performance has truly improved, especially in light of increasing corruption cases each year. The study uses panel data covering 500 regions in Indonesia over a 5-year period (2018-2022). This is an analysis technique applied Structural Equation Modeling Partial Least Square (SEM-PLS) with WARP-PLS software. The findings reveal that local government performance benefits greatly from public welfare. These findings indicate that public welfare represents the standard against which local government actions are judged